PERBANDINGAN PENGARUH LATIHAN KNEE-TUCK JUMP DAN DOUBLE LEG BOUND TERHADAP EXPLOSIVE POWER OTOT TUNGKAI PADA TIM BOLAVOLI PUTRA PENDOR - Luthfi Arzit; Slamet Slamet; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: This research was conducted to determine whether there Comparisons Exercise Influence Knee-Tuck Jump and Double Leg Bound To Explosive Muscle Power Limbs at a volleyball game so that when doing a smash to get maximum results.This research is a form of research with experimental treatment (Experimental), in this study all population of 24 people. The instruments used in this research is a test jump camdi. Afterthat, the data is processed with the statistics, to test the normality of the test at significant level 0,05α lilifors. Homogeneity test is then performed also aimed to see whether the two groups are in a homogeneous state. Hypothesis is 1) There is the influence of knee-tuck jump exercise to increase explosive leg muscle power on the volleyball Pendor team. 2) There is a double leg jump exercise influence on the increase of explosive leg muscle power on volleyball Pendor team. 3) There are differences in the effects of exercise knee-tuck jumps dandouble leg jump means the leg muscles of explosive power on volleyball Pendor team.Based on data analysis and discussion, it can be concluded that:1) There Knee tuck jump exercise influence on explosive leg muscle power in volleyball Pendor team proved with 7647 Thitung> Ttabel2.201 at α = 0.05.2) There is a double-leg exercises influence bound to explosive leg muscle power in volleyball Pendor team proved with 12,184 Thitung> Ttabel 2.201 at α = 0.05.There are differences in the effects of exercise and exercise Knee tuck jumps Double leg bound to the ability of explosive leg muscle power in volleyball Pendor team, where training Knee tuck jumps better use than to exercise Double leg bound to increase explosive leg muscle power, in terms of average, that the average Knee tuck jump exercise better use than to exercise Double leg bound.Keywords: Knee-Tuck Jump, Double Leg Bound, Explosive Muscle Power Limbs